2011
DOI: 10.9721/kjfst.2011.43.6.742
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microwave Treated-Wild Ginseng on the Quality of Korean Traditional Yakju

Abstract: AbstractsTo increase the quality of Korean traditional yakju, we prepared seed cultures by fermentation at 20 o C for 2 days after addition of 140% water, 3% nuruk and 1.5% yeast into cooked rice. After the 200% cooked rice, 120% water and 0.08% commercial saccharifying enzyme were added to seed cultures and fermented for 2 days at 20 o C, wild ginseng was added and then further fermented for 5 days. Physicochemical properties of traditional yakju were investigated. Ethanol was produced (18.5%) by the addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Of all the strains, except AO 2-6, the highest glucoamylase activity was exhibited when inoculated with 3% liquid starter, indicating the optimum condition for starter production. These results are consistent with those reported previously, wherein an excessively increased liquid starter concentration lowered glucoamylase activities [4,22]. In addition, it was confirmed that AN strains exhibited higher glucoamylase activity than AO strains.…”
Section: Enzyme Activitysupporting
confidence: 93%
See 2 more Smart Citations
“…Of all the strains, except AO 2-6, the highest glucoamylase activity was exhibited when inoculated with 3% liquid starter, indicating the optimum condition for starter production. These results are consistent with those reported previously, wherein an excessively increased liquid starter concentration lowered glucoamylase activities [4,22]. In addition, it was confirmed that AN strains exhibited higher glucoamylase activity than AO strains.…”
Section: Enzyme Activitysupporting
confidence: 93%
“…Most of the general bacteria were detected (or not) under both drying conditions, depending on the liquid starter inoculation concentration (Table 2). It is presumed that the inhibitory effect on the growth of spoilage bacteria resulted from the superiority of using a single strain [4]. The presence of Penicillium spp.…”
Section: Microbial Contamination and Spore Countmentioning
confidence: 99%
See 1 more Smart Citation